Environment-friendly mortar composition
By using high -content mineral adhesives and aggregate in the mortar composition, and adding an appropriate amount of additives, the problem of insufficient mineral adhesive performance in existing technology, realizing high -performance, low environmental impact mortar products Essence
Patent Information
- Application Number
- CN202380047629.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-28
AI Technical Summary
It is difficult to develop a fully prepared mortar product with little impact on the environment and excellent performance in the prior art, especially when using auxiliary cement materials, the performance of mineral adhesives is insufficient.
Mortar compositions containing 15WT. %-50WT. % Of mineral adhesives. Among them, mineral adhesive consists of 40-70 cement and 30-60 weight-based cement alternatives based on clay, limestone and gypsum. And add 50WT. %-80wt. % And 0wt. %-10WWT. % Additives.
The significant improvement of the mortar composition in terms of processability, hardening state, mechanical performance and durability, reduced production costs and environmental impacts, and applied to various buildings applications.
Smart Images

Figure BDA0005191530970000151 
Figure BDA0005191530970000161
Abstract
Description
Technical Field
[0001] The present invention relates to mortar compositions based on limestone, clay, gypsum and cement. Furthermore, the present invention relates to a workable mortar composition and a hardened mortar composition obtainable by hardening the workable mortar composition. Further aspects of the present invention relate to a method for preparing the mortar composition and the use of the mortar composition for a specific application. Background Art
[0002] In the construction industry, a large amount of cement-based materials are used, such as, for example, mortar or concrete. However, cement production is an energy-intensive process, accounting for a significant amount of the world's carbon dioxide (CO2) emissions. In order to reduce carbon dioxide emissions, the cement in the binder composition can be partially replaced by so-called supplementary cementitious materials (SCM). These are, for example, pozzolanic materials, such as, for example, powdered fly ash or natural pozzolans, latent hydraulic products such as ground granulated blast furnace slag, or even inert materials, such as, for example, limestone.
[0003] Although replacing such cements with SCMs may be able to partially overcome the energy consumption problem in cement production, the resulting mineral binders generally lack performance compared to ordinary Portland cement (OPC).
[0004] However, in recent years, some auxiliary cementitious materials such as fly ash and ground granulated blast furnace slag have become scarce. Therefore, alternative solutions based on sufficiently abundant materials have been developed.
[0005] In this regard, an attractive development is the so-called "LC3 adhesive". These are cementitious mineral adhesives that are partly composed of Portland cement and partly of cement substitutes. Thus, the cement substitute is based on a combination of calcined clay, limestone and gypsum. The method enables a high level of replacement of cement in the mineral adhesive, i.e. about 50 wt.%. Despite the high degree of replacement of cement, LC3 adhesives are characterized by sufficiently good mechanical properties and a fairly high durability. At the same time, production costs and environmental impact can be reduced.
[0006] However, until today, there are no known satisfactory fully formulated mortar products suitable for practical use, such as for example grouting or repair mortars based on LC3 binders. Summary of the invention
[0007] The object of the present invention is to provide a mortar composition which is suitable for practical applications and has as little negative impact on the environment as possible. However, the mortar composition should have advantageous properties, especially with regard to workability, curing, mechanical strength and / or durability.
[0008] Surprisingly, it has been found that these objects are achieved by the features of claim 1. The core of the invention is therefore a mortar composition comprising:
[0009] a) 15 wt.% to 50 wt.% of a mineral binder, wherein:
[0010] - the mineral binder comprises 40-70 parts by weight of cement and 30-60 parts by weight of a cement substitute based on clay, limestone and gypsum, relative to 100 parts by weight of the mineral binder,
[0011] - and wherein, relative to 100 parts by weight of the cement substitute, the cement substitute comprises:
[0012] 35-65 parts by weight of clay, especially calcined clay,
[0013] 1-20 parts by weight of gypsum, and
[0014] Limestone to make up to 100 parts by weight;
[0015] b) 50 wt.% - 80 wt.%, in particular 62 wt.% - 65 wt.% of aggregate, in particular sand;
[0016] c) 0 wt.% to 10 wt.%, especially 0 wt.% to 6 wt.% of one or more additives;
[0017] - wherein all wt. % are relative to the dry weight of the mortar composition.
[0018] The mortar compositions of the invention have proven to be highly beneficial. In particular, they are good in terms of workability and hardened state, they are characterized by good mechanical properties and excellent durability. In particular, the mechanical strength of the hardened mortar after 28 days is at a level suitable for a wide range of applications. Furthermore, the shrinkage during hardening is at a low level, so that for most applications, no shrinkage reducer is required. With regard to durability, the sulfate resistance of the mortar is at a high level, while the carbonation is low. Due to the significant proportion of cement substitutes, the carbon footprint of the mortar composition and the products produced therefrom is much lower when compared with ordinary cementitious mortars.
[0019] Due to the beneficial properties, the mortar of the present invention can be used in a variety of different applications. For example, the mortar of the present invention can be formulated and used as a cementitious tile adhesive, a grouting material, a self-leveling lining, a self-leveling covering, a render, a repair mortar, a masonry screed or concrete, a mortar primer, a wall leveling agent for interior or exterior, a non-shrink grout, a screed, a waterproof mortar and / or an anchoring mortar.
[0020] Although the mineral binder of the mortar composition of the present invention comprises a relatively high proportion of cement substitutes based on clay, especially calcined clay, gypsum and limestone, the mortar composition is highly suitable for practical use and has comparable properties to conventional mortar compositions based on pure cement binder. Without being bound by theory, it is believed that the specific components and their proportions are responsible for these unexpected findings.
[0021] Further aspects of the invention are subject matter of further independent claims.Particularly preferred embodiments are outlined throughout the description and in the dependent claims. DETAILED DESCRIPTION
[0022] A first aspect of the present invention relates to a mortar composition comprising:
[0023] a) 15 wt.% to 50 wt.% of a mineral binder, wherein:
[0024] - the mineral binder comprises 40-70 parts by weight of cement and 30-60 parts by weight of a cement substitute based on clay, limestone and gypsum, relative to 100 parts by weight of the mineral binder,
[0025] - and wherein, relative to 100 parts by weight of the cement substitute, the cement substitute comprises:
[0026] 35-65 parts by weight of clay, especially calcined clay,
[0027] 1-20 parts by weight of gypsum, and
[0028] Limestone to make up to 100 parts by weight;
[0029] b) 50 wt.% - 80 wt.%, in particular 62 wt.% - 65 wt.% of aggregate, in particular sand;
[0030] c) 0 wt.% to 10 wt.%, especially 0 wt.% to 6 wt.% of one or more additives;
[0031] - wherein all wt. % are relative to the dry weight of the mortar composition.
[0032] The cement present in the mineral binder preferably comprises or consists of Portland cement, aluminate cement and / or sulphoaluminate cement.
[0033] In particular, the mineral binder of the present invention comprises not more than 5 wt.%, preferably not more than 2 wt.% of calcium aluminate cement and / or calcium sulphoaluminate cement relative to the total dry weight of the mineral binder.
[0034] In particular, the content of Portland cement in the mineral binder of the present invention is higher than the content of calcium aluminate cement and / or calcium sulfoaluminate cement.
[0035] The most preferred cement is Portland cement, in particular cement of type CEM I according to standard EN 197.
[0036] The term "aluminate cement" particularly denotes a cement having an aluminum content (measured as Al2O3) of at least 30 wt.%, especially at least 35 wt.%, in particular 35 wt.% - 58 wt.%. Preferably, the aluminate cement is an aluminate cement according to standard EN 14647: 2006. Preferably, the sulphoaluminate cement is a calcium sulphoaluminate cement.
[0037] "Clay" within the context of the present invention is a solid material which constitutes at least 30 wt.%, preferably at least 35 wt.%, in particular at least 75 wt.% of clay minerals (each with respect to their dry weight). Such clay minerals preferably belong to the kaolinite group (such as kaolinite, dickite, mica or nacrite), the montmorillonite group (such as montmorillonite, nontronite or saponite), the vermiculite group, serpentine, palygorskite, sepiolite, chlorite, talc, pyrophyllite, mica (such as biotite, muscovite, illite, glauconite, chrysocolla and polysilicon muscovite) or mixtures thereof. Clay minerals belonging to the kaolinite group, in particular kaolinite and mica, in particular muscovite and illite, and mixtures thereof are particularly preferred.
[0038] Clay within the context of the present invention may be any type of clay, such as raw clay and / or calcined clay.
[0039] Raw clay is clay mineral which has been extracted, for example, from a quarry, optionally purified and optionally dried.
[0040] The calcined clay can be, for example, a low temperature calcined clay and / or a high temperature calcined clay. Low temperature calcined clay is a clay that has been heat treated at a temperature of 500°C-1200°C. Such low temperature calcination typically results in the removal of interlayer water and at least partial, preferably complete, dehydroxylation. For example, the low temperature calcined clay mineral can be produced in a rotary kiln or in a flash calciner. High temperature calcined clay is a clay mineral that has been heat treated at a temperature above 1200°C and typically 1300°C-1400°C. High temperature calcined clay is typically crystalline or contains a large amount of crystalline phases, especially mullite.
[0041] The clay within the context of the present invention is preferably a calcined clay, especially a low temperature calcined clay. Low temperature calcined clay is a clay material that has been heat treated, preferably at a temperature of 500°C to 1200°C, or in a flash calcination process at a temperature of 800°C to 1100°C. Suitable flash calcination processes are described, for example, in WO 2014 / 085538. Low temperature calcined clay is an anhydrous material.
[0042] It is preferred within the context of the present invention that during calcination of the clay, the clay material is dehydroxylated to an amorphous material while preventing the formation of a crystalline high temperature aluminosilicate phase such as mullite.
[0043] Low temperature calcined clays and especially low temperature calcined kaolinite are generally amorphous, have a significantly higher specific surface area than the original clay, and have pozzolanic activity.
[0044] According to an embodiment, the calcined clay is produced by heat treatment separately from the other components of the binder composition and in particular separately from the Portland cement and / or other pozzolanic and / or latent hydraulic materials present.
[0045] Calcined clays, and especially calcined kaolinite, are generally amorphous, have a significantly higher specific surface area than the original clay, and are pozzolanic.
[0046] In particular, the clay comprises or consists of a calcined clay from the kaolin, montmorillonite and / or illite groups. In particular, the calcined clay is selected from metakaolin, calcined illite and / or calcined montmorillonite.
[0047] According to a particularly preferred embodiment of the present invention, the calcined clay is metakaolin. Metakaolin is a material resulting from the calcination of kaolinite or a kaolinite-rich mineral (e.g. having a kaolinite content of at least 30 wt.%, preferably to at least 35 wt.%, relative to its dry weight). The calcination temperature for making metakaolin is typically in the range of 500°C-900°C.
[0048] According to an embodiment, the clay, especially calcined clay, is ground to a powder having at least 0.5 wt.%, preferably at least 2 wt.%, still more preferably at least 10 wt.%, especially at least 20 wt.% of 45 μm residue as measured according to ASTM C 430-96 (2003).
[0049] In particular, the gypsum comprises calcium sulfate hemihydrate and / or anhydrite. Calcium sulfate hemihydrate (CaSO4.0.5H2O) can be present as α-hemihydrate or β-hemihydrate. Anhydrite is in particular anhydrite II and / or anhydrite III.
[0050] According to the embodiment, limestone means calcium carbonate (CaCO 3 ). In a preferred embodiment of the present invention, the chemical composition of limestone is as defined in standard EN 197-1:2011. In alternatives, limestone may also mean magnesium carbonate, dolomite, and / or a mixture of magnesium carbonate, dolomite, and / or calcium carbonate. It is particularly preferred that limestone in the context of the present invention is a naturally occurring limestone that is mainly composed of calcium carbonate (typically calcite and / or aragonite) but typically also contains some magnesium carbonate and / or dolomite. Limestone may also be a naturally occurring marl.
[0051] In the context of the present invention, limestone is in particular an unheat-treated ground material. In particular, the limestone is not decarbonated. According to an embodiment, the limestone has a carbon content of 3000-15000 cm 2 The Blaine surface is measured as described in standard EN 196-6:2010.
[0052] In particular, the limestone of the cement substitute has a D50 particle size of 1-125 μm. The D50 particle size means that 50% of the particles are smaller than the specified value and 50% are larger than the specified value. In particular, the particle size distribution of the limestone of the cement substitute is such that both the particle size D2 and the particle size D98 are within the range of 1-125 μm.
[0053] Similar to the D50 particle size described above, a D98 particle size means that 98% of the particles are smaller than the specified value and 2% are larger than the specified value. Thus, a D2 particle size means that 2% of the particles are smaller than the specified value and 98% are larger than the specified value.
[0054] The mineral binders cement, clay, gypsum and limestone are present in particular in powder form.
[0055] In particular, the Blaine fineness of the mineral binder in the mortar composition is 300-6000 μm. 2 / g, especially 1000-4500m 2 / g, especially 2000-4000m 2 / g. Blaine fineness is measured as described in standard EN 196-6:2010.
[0056] Aggregate includes any type of mortar aggregate. In particular, the aggregate is 2.0-3.0 kg / dm 3 The density is characterized.
[0057] The particle size of the aggregate is preferably 0.01-8 mm, especially 0.03-4 mm, preferably 0.05-2 mm, in particular 0.08-1 mm.
[0058] Within the context of the present invention, the particle size of particles equal to or greater than 0.1 mm can be determined by sieve analysis, in particular with a sieve characterized by square openings. In particular, the particle size is represented by the opening size of the test sieve through which the particles in question just pass.
[0059] According to the sieve analysis, the size of the particles having a size less than 0.1 mm can be determined by laser diffraction as described in ISO 13320:2009. Preferably, the particle size of the non-spherical or irregular particles is expressed by the equivalent spherical diameter of a sphere of equivalent volume. In particular, the lower limit value of the range given for the particle size represents the D1 value, while the upper limit value of the range given for the particle size represents the D99 value. In other words, in this case, 1% of the particles have a smaller particle size than the lower limit value of the range, while 1% of the particles have a larger particle size than the upper limit value of the range.
[0060] In particular, the aggregate comprises sand, quartz and / or calcium carbonate. Most preferably sand. In case calcium carbonate is used as aggregate, such calcium carbonate is chemically and / or physically different from the other components of the mortar composition. In particular, if calcium carbonate is used as aggregate, it is chemically and / or physically different from the limestone of the cement substitute and / or from the hardening accelerator.
[0061] In particular, the calcium carbonate as aggregate has a D50 particle size > 125 μm, while the D50 particle size of the limestone in the cement substitute is 1-125 μm. Also preferably, the D98 particle size of the limestone in the cement substitute is smaller than the D2 particle size of the calcium carbonate used as aggregate.
[0062] In particular, the mortar composition is present as a dry particulate material, in particular a dry powder, before mixing with water.
[0063] In particular, the mineral binder is present in a proportion of 32-50 wt.%, preferably 35-50 wt.%, more preferably 35-38 wt.%, especially 35-37 wt.%, relative to the dry weight of the mortar composition. These proportions prove to be highly beneficial.
[0064] According to a highly preferred embodiment, the cement substitute comprises, relative to 100 parts by weight of the cement substitute:
[0065] 35-45, especially 37-42 parts by weight of clay, especially calcined clay,
[0066] 3-10, especially 4-7 parts by weight of gypsum;
[0067] Make up to 100 parts by weight of limestone.
[0068] In particular, the cement substitute comprises 40 parts by weight of clay, in particular calcined clay, 5 parts by weight of gypsum and 55 parts by weight of limestone, relative to 100 parts by weight of the cement substitute.
[0069] In the case of these ratios, the advantages of the invention are even more pronounced.
[0070] However, for specific applications, other proportions may also be suitable. For example, in another embodiment, the cement substitute comprises 63 parts by weight of clay, especially calcined clay, 7 parts by weight of gypsum and 30 parts by weight of limestone, relative to 100 parts by weight of the cement substitute.
[0071] The one or more additives that may optionally be present in the mortar composition are in particular concrete, mortar and / or grout admixtures as defined according to EN 934-2:2009+A1:2012. For example, the one or more additives are selected from setting time regulators, accelerators, retarders, air entraining agents, defoamers, shrinkage reducers, rheology modifiers, thixotropic agents, corrosion inhibitors, preservatives, chrome reducing agents, fibers, stabilizers and / or dyes.
[0072] In a further preferred embodiment, the mortar composition comprises a hardening accelerator additive, in particular a calcium compound, such as calcium oxide and / or calcium carbonate.
[0073] The hardening accelerator additive, especially calcium carbonate, is chemically and / or physically different from the other components of the mortar composition. In particular, if calcium carbonate is used as a hardening accelerator additive, it is chemically and / or physically different from the limestone and aggregates of the cement substitute.
[0074] In particular, the hardening accelerator additive is present in the form of a powder having a particle size smaller than the particle size of the limestone of the cement substitute. Thus, preferably, the particles of the hardening accelerator additive have a D50 particle size smaller than the D50 particle size of the limestone of the cement substitute. Also preferably, the particles of the hardening accelerator additive have a D98 particle size smaller than the D2 particle size of the limestone of the cement substitute.
[0075] The particle size can be determined in particular by laser diffraction, preferably according to Standard ISO 13320:2009.
[0076] The proportion of hardening accelerator additives is preferably 0.001 wt.% - 2 wt.%, in particular 0.01 wt.% - 1 wt.%, relative to the dry weight of the mortar composition. Such additives allow increasing the early strength of the mortar composition, for example 1 day after mixing with water.
[0077] In particular, the hardening accelerator additive is present in the form of a powder, in particular with a D98 particle size of <25 μm, in particular <15 μm, in particular <10 μm, in particular <5 μm. Thus, preferably, the D50 particle size of the hardening accelerator additive is <5 μm, in particular <2 μm. These particle sizes are particularly effective for accelerating the hardening of the mortar composition of the invention.
[0078] If calcium carbonate in the form of a powder is used as a hardening accelerator additive, the D50 particle size of the calcium carbonate is preferably <1 μm, especially <0.9 μm. Thus, in particular, the D98 particle size of the calcium carbonate is <5 μm, especially <2 μm.
[0079] In particular, calcium carbonate or limestone can be used as:
[0080] - as a hardening accelerator additive with a calcium carbonate D50 particle size of <1 μm; and / or
[0081] - as a component of a cement substitute having a D50 particle size of 1-125 μm; and / or
[0082] - As aggregate with a D50 particle size > 125 μm.
[0083] In particular, the particle size distribution of the limestone of the cement substitute is such that both the particle size D2 and the particle size D98 are in the range of 1-125 μm. Also preferably, the D98 particle size of the calcium carbonate of the hardening accelerator additive is smaller than the D2 particle size of the limestone in the cement substitute, and the D98 particle size of the limestone in the cement substitute is smaller than the D2 particle size of the calcium carbonate used as aggregate.
[0084] In particular, the mortar composition comprises a plasticizer additive. The plasticizer additive may be selected from the group of lignin sulfonates, gluconates, naphthalene sulfonates, melamine sulfonates, vinyl copolymers and / or polycarboxylate ethers. Polycarboxylate ethers are most preferred.
[0085] The polycarboxylate ethers are in particular comb polymers having a polycarboxylate backbone and side chains, wherein the side chains are preferably bound to the polycarboxylate backbone via ester, ether, amide and / or imide groups. Ester, ether and / or amide groups are preferred, especially ester and / or ether groups.
[0086] The backbone has at least one acid unit or a salt thereof. The acid unit is in particular an alpha-unsaturated monocarboxylic acid or dicarboxylic acid, such as acrylic acid, methacrylic acid, maleic anhydride, maleic acid, itaconic acid, crotonic acid, or fumaric acid. The acid unit is preferably acrylic acid, methacrylic acid, maleic acid and / or a salt thereof and / or a combination thereof.
[0087] The side chains are preferably attached to (meth)acrylate, vinyl ether, (meth)allyl ether and / or prenol ether monomers polymerized with at least one acid unit of the backbone.
[0088] More particularly, the side chains comprise polyalkylene oxide side chains, preferably polyethylene oxide side chains. Preferably at least 50 mol %, more particularly at least 75 mol %, preferably at least 95 mol % or 100 mol % of the side chains contain or consist of polyalkylene oxide.
[0089] The fraction of ethyleneoxy units in the polyalkylene oxide side chains is preferably greater than 90 mol %, more particularly greater than 95 mol %, preferably greater than 98 mol % and especially 100 mol %, based on all alkyleneoxy units present in the side chains.
[0090] The polyalkylene oxide side chains are particularly of the formula -[AO] n -R a In this formula, in particular,
[0091] -A is C2 to C5 alkylene, which may be branched or unbranched. Most preferably A is C2 alkylene; and / or
[0092] -R a Preferably H or C1 to C 20 Alkyl, cyclohexyl, or alkylaryl; and / or
[0093] - advantageously, n is from 2 to 300, more particularly from 10 to 200 or from 15 to 150, especially 25-70; and / or
[0094] -The number average molecular weight of the side chain (M n ) is 500-6000, especially 1000-4000, in particular 2000-3000 g / mol, and / or
[0095] -The weight average molecular weight (M w ), especially 5000-150000 g / mol, preferably 10000-100000 g / mol, and / or
[0096] -The number average molecular weight (M) of the polycarboxylate ether n ) is advantageously 3000-100000 g / mol, more particularly 8000-70000 g / mol.
[0097] The weight average molecular weight is determined by gel permeation chromatography (GPC) using polyethylene glycol (PEG) as standard. This technique itself is known to the person skilled in the art.
[0098] Particularly preferred are comb polymers having a molar ratio of one or more acid units to side chains of 0.5 to 5, in particular 1 to 4, especially 2.5 to 4. This gives mortar compositions having good processability or flowability, respectively, which is maintained even for a relatively long time, for example up to 60 minutes.
[0099] Therefore, preferably, the number average molecular weight (M n ) is 500-6000, especially 1000-4000, especially 2000-3000 g / mol.
[0100] According to an embodiment, the comb polymer comprises (meth)acrylic monomers carrying side chains and vinyl ether, (meth)allyl ether and / or isoprenol ether monomers. In particular, the comb polymer comprises (meth)acrylic monomers carrying side chains and (meth)allyl ether monomers.
[0101] Methods for preparing such comb polymers are known in the art. Two main methods are used industrially for synthesizing such comb polymers. The first method is the free radical polymerization of ethylenically unsaturated monomers. The side chains of the resulting comb polymers are already attached to the monomer units. Comb polymers with desired structures and properties are obtained by specific selection and ratio of monomers in the polymerization reaction solution.
[0102] In the second method called polymer analogous reaction, a polycarboxylic acid backbone is synthesized in a first step. Subsequently, side chains are attached to the polycarboxylic acid backbone, for example, by esterification, amidation or etherification reaction with alcohols, amines, etc. Such polymer analogous reactions and resulting comb polymers are described in, for example, WO 97 / 35814, WO 95 / 09821, DE 100 15 135A1, EP 1138 697A1, EP 1 348 729A1 and WO 2005 / 090416. Details about polymer analogous reactions are disclosed in, for example, EP 1 138 697 B1, page 7, line 20 to page 8, line 50 and in an embodiment thereof, or EP 1 061 089 B1, page 4, line 54 to page 5, line 38 and in an embodiment thereof.
[0103] Corresponding comb polymers are also marketed by Sika Schweiz AG under the trade name TU-100 series. Commercial sales.
[0104] Preferably, the proportion of the plasticizer additive is 0.001 wt.%-2 wt.%, especially 0.01 wt.%-1 wt.%, relative to the dry weight of the mortar composition.
[0105] Plasticizers may be used to adjust the workability and open time of the mortar composition after mixing with water.
[0106] It is further preferred that a retarder additive is present in the mortar composition. Preferably, the retarder additive is selected from boric acid, salts of boric acid, salts of phosphoric acid, sorbitol, sugars and / or hydroxycarboxylic acids.
[0107] In particular, the retarder additive is a hydroxycarboxylic acid and / or a salt thereof, particularly preferably a gluconate, most preferably sodium gluconate.
[0108] Preferably, the proportion of the retarder additive is 0.0001 wt.%-0.1 wt.%, especially 0.001 wt.%-0.05 wt.%, relative to the dry weight of the mortar composition.
[0109] Retarder additives allow controlling the open time of the mortar composition after mixing with water or the time for which the mortar remains workable, respectively.
[0110] Particularly preferably, a retarder additive is added to the mortar composition if the weight proportion of clay, especially calcined clay, especially metakaolin in the cement substitute is at least 40 parts by weight relative to the total weight of the cement substitute. As demonstrated, clay, especially calcined clay, in the cement substitute, especially in a proportion of 40 or more parts by weight, can significantly shorten the open time. If this is to be prevented, a retarder additive can be used.
[0111] With regard to highly preferred mortar compositions:
[0112] - the mineral binder is present in a proportion of 35 wt.% to 37 wt.% relative to the dry weight of the mortar composition;
[0113] - Relative to 100 parts by weight of the cement substitute, the cement substitute comprises:
[0114] 37-42 parts by weight of clay, especially calcined clay,
[0115] 4-7 parts by weight of gypsum;
[0116] Limestone to make up to 100 parts by weight;
[0117] - Optionally, the mortar comprises 0.01 wt.% to 1 wt.% of a plasticizer additive, in particular a polycarboxylate ether as described above, relative to the dry weight of the mortar composition;
[0118] - Optionally, the mortar comprises 0.01 wt.% to 1 wt.% of a calcium compound, in particular calcium oxide and / or calcium carbonate powder, relative to the dry weight of the mortar composition, wherein the calcium compound is chemically and / or physically different from the other components of the mortar composition, in particular the calcium compound has a D98 particle size smaller than the D98, more preferably the D2 particle size, of the limestone of the cement substitute;
[0119] - Optionally, the mortar comprises 0.001 wt.% - 0.05 wt.% of a retarder additive, especially a hydroxycarboxylic acid and / or a salt thereof, in particular sodium gluconate, relative to the dry weight of the mortar composition.
[0120] Therefore, preferably, at least the plasticizer additive is present in the above mentioned proportions.
[0121] A preferred mortar composition comprises:
[0122] a) 35 wt.% to 50 wt.% of a mineral binder, wherein:
[0123] - the mineral binder comprises 40-70 parts by weight of cement and 30-60 parts by weight of a cement substitute based on clay, limestone and gypsum, relative to 100 parts by weight of the mineral binder;
[0124] - and wherein, relative to 100 parts by weight of the cement substitute, the cement substitute comprises:
[0125] 35-65 parts by weight of clay, especially calcined clay,
[0126] 1-20 parts by weight of gypsum, and
[0127] Limestone to make up to 100 parts by weight;
[0128] b) 50wt.%-65wt.% of aggregate, especially sand;
[0129] c) 0wt.%-10wt.% of one or more additives;
[0130] - wherein all wt. % are relative to the dry weight of the mortar composition.
[0131] A preferred mortar composition comprises:
[0132] a) 35 wt.% to 37 wt.% of a mineral binder, wherein:
[0133] - the mineral binder comprises 40-70 parts by weight of cement and 30-60 parts by weight of a cement substitute based on clay, limestone and gypsum, relative to 100 parts by weight of the mineral binder;
[0134] - and wherein, relative to 100 parts by weight of the cement substitute, the cement substitute comprises:
[0135] 35-65 parts by weight of clay, especially calcined clay,
[0136] 1-20 parts by weight of gypsum, and
[0137] Limestone to make up to 100 parts by weight;
[0138] b) 63wt.%-65wt.% of aggregate, especially sand;
[0139] c) 0wt.%-10wt.% of one or more additives;
[0140] - wherein all wt. % are relative to the dry weight of the mortar composition.
[0141] In particular, the mortar composition is a cementitious tile adhesive, a grouting material, a self-leveling underlayment, a self-leveling covering, a render, a repair mortar, a masonry thin-joint mortar or concrete, a mortar primer, a wall leveling agent for interior or exterior, a non-shrink grout, a thin-joint mortar, a waterproof mortar, or an anchoring mortar.
[0142] Cementitious tile adhesives are in particular in accordance with standard EN 12004-1. Grouting materials are in particular in accordance with standard EN 13888. Self-leveling underlays or self-leveling coverings are in particular in accordance with standard EN 13813. Renderings are in particular in accordance with standard EN 998-1. Repair mortars are in particular in accordance with standard EN 1504-3. Masonry mortars or concrete are in particular in accordance with standards EN 998-2 and EN 206-1. Mortar primers are in particular in accordance with standard EN 13813. Non-shrinkage grouts are in particular in accordance with standard EN 1504-6. Thin-joint mortars are in particular in accordance with standard EN 998-2. Waterproof mortars are in particular in accordance with standard EN 1504-2. Anchoring mortars are in particular in accordance with standard EN 1504-6.
[0143] According to a preferred embodiment, the dry mortar composition is a one-component mixture. This means that all individual materials and / or substances are mixed with one another in one container. One-component compositions are particularly easy to handle and exclude the risk of mixing or incorrect metering of the individual components by the user.
[0144] However, in principle a two-component mortar composition or even a multi-component mortar composition can be provided. The first component can, for example, be present in a first container comprising a mineral binder. The second component, which is present in a second container, can comprise aggregate. Other distributions are also possible. A two-component or multi-component mortar composition allows, for example, the mortar composition to be adjusted for a specific application.
[0145] Another aspect of the present invention relates to a processable mortar composition comprising a mortar composition as described above and water. Thus, preferably, the weight ratio of water to mineral binder is 0.25-0.7, especially 0.3-0.5. The proportion of water can be selected depending on the desired application.
[0146] A further aspect of the invention relates to a hardened mortar composition obtainable by hardening the workable mortar composition as described above.
[0147] In yet another aspect, the present invention relates to the use of the dry mortar composition as described above or the processable mortar composition as described above as a cementitious tile adhesive, a grouting material, a self-leveling lining, a self-leveling covering, a render, a repair mortar, a masonry thin-joint mortar or concrete, a mortar primer, a wall leveling agent for interior or exterior, a non-shrink grout, a thin-joint mortar, a waterproof mortar, or an anchoring mortar.
[0148] Furthermore, the present invention relates to a method for preparing a mortar composition as described above, wherein 15 wt.%-50 wt.%, preferably 32 wt.%-50 wt.%, more preferably 35 wt.%-50 wt.%, still more preferably 35 wt.%-38 wt.%, in particular 35 wt.%-37 wt.% of a mineral binder as defined above is mixed with 50 wt.%-80 wt.%, preferably 50 wt.%-68 wt.%, more preferably 50 wt.%-65 wt.%, still more preferably 62 wt.%-65 wt.%, in particular 63 wt.%-65 wt.%, of aggregate, in particular sand, and optionally 0-10 wt.%, in particular 0-6 wt.% of one or more additives as defined above, wherein all wt.% are relative to the total dry weight of the mortar composition.
[0149] In order to obtain a mortar composition in a workable state, water having a weight ratio of water to mineral binder of 0.25 to 0.7, in particular 0.3 to 0.5, can be mixed with the other components of the mortar composition.
[0150] Further advantageous configurations of the invention are apparent from the exemplary embodiments.
[0151] Exemplary embodiments
[0152] Grouting composition
[0153] As indicated in Tables 1 and 2, dry high strength grouting compositions based on mineral binder and sand (0-2.2 mm) were prepared.
[0154] The mineral binder of Examples A, C, D, E, F, G, H and I consists of 48 parts by weight of Portland cement and 52 parts by weight of cement substitute, relative to 100 parts by weight of the mineral binder, wherein the cement substitute consists of 37 parts by weight of calcined clay (metakaolin), 5 parts by weight of gypsum and 58 parts by weight of limestone, relative to 100 parts by weight of the mineral binder. The mineral binder of Example B consists of 50 parts by weight of Portland cement and 50 parts by weight of cement substitute, wherein the cement substitute consists of 40 parts by weight of calcined clay (metakaolin), 5 parts by weight of gypsum and 55 parts by weight of limestone, relative to 100 parts by weight of the mineral binder.
[0155] Thus, the amounts of Portland cement, calcined clay, gypsum and the total amount of calcium carbonate (derived from the mineral binder and fine calcium carbonate) were the same in all Examples AI.
[0156] The first plasticizer P1 used in the composition is a comb polymer based on acrylic acid monomers and polyethylene glycol methallyl ether monomers. Thus, the polyethylene glycol methallyl ether monomer has an average molecular weight of 2400 g / mol, and the molar ratio of one or more acid units to side chains is 3.5. The second plasticizer P2 used in the composition is a similar comb polymer having a molar ratio of one or more acid units to side chains of 5.6 instead of 3.5.
[0157] The grouting composition was mixed with water (weight ratio of water to total weight of dry mortar composition = 0.38) in order to obtain a workable grouting composition.
[0158] Thereafter, the flow table spreadability values (FTS) of the processable compositions after mixing with water were evaluated at the time intervals indicated in Tables 1 and 2 according to standard EN 12350-5:2009 (without 15 strokes).
[0159] Determination of compressive strength (in N / mm2) using a prism (40×40×160 mm) according to EN 196-1:2016 and EN 12190:1998 2 as a unit) test.
[0160] Tables 1 and 2 give an overview of the grout compositions and their properties.
[0161] Table 1
[0162]
[0163] 1) Comb polymer P1
[0164] 2) Comb polymer P2
[0165] * OmyaCarb Extra GU (available from Omya; D98 = 4 μm, D50 = 0.9 μm)
[0166] # Thickener, defoamer
[0167] nm = unmeasurable
[0168] Table 2
[0169]
[0170] 1) Comb polymer P1
[0171] 2) Comb polymer P2
[0172] * OmyaCarb Extra GU (available from Omya; D98 = 4 μm, D50 = 0.9 μm)
[0173] # Thickener, defoamer
[0174] nm: unmeasurable
[0175] As is apparent from the data in Tables 1 and 2, the grout composition exhibits flow behavior that allows for easy processing and injection as a grout.
[0176] Notably, when using comb polymer P1 having a molar ratio of one or more acid units to side chains of 3.5 (Examples AC), processability or flow table spreadability can be maintained at a higher level for a longer time, respectively, when compared to comb polymer P2 (Example D). Likewise, the use of a retarder helps to improve processability (see Examples E and F).
[0177] When using fine calcium carbonate as an accelerator additive, the compressive strength after 24 hours can be improved when compared to a composition comprising the same amount of coarse calcium carbonate (see Examples A and B).
[0178] Smaller amounts of mineral binder lead to an increase in FTS, but also to a significant decrease in the compressive strength after 24 hours (see Examples D, G and H). An amount of 60 wt. % binder relative to the dry weight of the mortar did not lead to a workable mixture.
[0179] Additional Tests
[0180] Compressive strength after 28 days: Compressive strengths up to 90 MPa were observed.
[0181] Adhesion properties: Adhesion tests carried out with the grouting composition on concrete substrates according to standard EN 1542: 1999 showed a bond strength of > 2 MPa after 28 days. Thus, the grouting composition of the invention is highly beneficial with regard to adhesion.
[0182] Physical properties (shrinkage / swelling): Shrinkage / swelling was determined according to EN 12617-4: 2002. At 91 days, the shrinkage / swelling was -0.5 / 0.2‰.
[0183] Carbonation: The carbonation depth was measured according to EN 13295:2004 and found to be 0 mm for the high strength grouting composition of the present invention. This is similar to the reference composition, which is based on a similar composition with a binder consisting of 100 parts by weight of Portland cement (no cement substitute). Therefore, the resistance of the mortar composition of the present invention to carbonation is as good as that of a normal mortar composition.
[0184] Sulfate resistance: The sulfate elongation of the high-strength grouting composition of the invention measured according to standard SIA 262 / 1:2019 after 12 weeks is 0.197‰. For a reference sample based on a similar composition with a binder consisting of 100 parts by weight of Portland cement (without cement substitute), the sulfate elongation is 0.541‰.
[0185] In summary, the grouting composition of the present invention shows highly beneficial properties, although being based on a composition with a low carbon footprint.
[0186] Those skilled in the art will appreciate that the present invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments disclosed herein are considered in all aspects to be illustrative and not restrictive.
Claims
1. A mortar composition comprising: a) 15 wt.% to 50 wt.% of a mineral binder, wherein: - the mineral binder comprises 40-70 parts by weight of cement and 30-60 parts by weight of a cement substitute based on clay, limestone and gypsum, relative to 100 parts by weight of the mineral binder; - and among them, Relative to 100 parts by weight of the cement substitute, the cement substitute comprises: 35-65 parts by weight of clay, especially calcined clay, 1-20 parts by weight of gypsum, and Limestone to make up to 100 parts by weight; b) 50 wt.% - 80 wt.%, in particular 62 wt.% - 65 wt.% of aggregate, in particular sand; c) 0wt.%-10wt.%, especially 0wt.%-6wt.% of one or more additives; All wt.% herein are relative to the dry weight of the mortar composition.
2. The mortar composition according to claim 1, wherein The mineral binder is present in a proportion of 32 wt.%-50 wt.%, preferably 35 wt.%-50 wt.%, more preferably 35 wt.%-38 wt.%, especially 35 wt.%-37 wt.%, relative to the dry weight of the mortar composition.
3. A mortar composition according to any one of the preceding claims, wherein: Relative to 100 parts by weight of the cement substitute, the cement substitute comprises: 35-45, especially 37-42 parts by weight of clay, especially calcined clay, 3-10, especially 4-7 parts by weight of gypsum; Make up to 100 parts by weight of limestone.
4. A mortar composition according to any one of the preceding claims, wherein: A hardening accelerator additive is present, in particular a calcium compound, such as calcium oxide and / or calcium carbonate powder, wherein the hardening accelerator additive is chemically and / or physically different from the other components of the mortar composition, and wherein the proportion of the hardening accelerator additive is 0.001 wt.%-2 wt.%, in particular 0.01 wt.%-1 wt.%, relative to the dry weight of the mortar composition.
5. A mortar composition according to any one of the preceding claims, wherein: There is a plasticizer additive comprising a polycarboxylate ether, wherein the polycarboxylate ether is a comb polymer having a polycarboxylate backbone and side chains, wherein the side chains are bonded to the polycarboxylate backbone via ester, ether, amide and / or imide groups, and the backbone has at least one acid unit or a salt thereof, and wherein the molar ratio of the one or more acid units to the side chains is 0.5 wt.% to 5 wt.%, particularly 1 wt.% to 4 wt.%, especially 2.5 wt.% to 4 wt.%.
6. A mortar composition according to any one of the preceding claims, wherein: A retarder additive is present, especially a hydroxycarboxylate, in particular sodium gluconate, wherein the proportion of the retarder additive is 0.0001 wt.%-0.1 wt.%, especially 0.001 wt.%-0.05 wt.%, relative to the dry weight of the mortar composition.
7. The mortar composition according to claim 6, wherein: The weight proportion of the clay, especially calcined clay, in the cement substitute is at least 40 parts by weight relative to the total weight of the cement substitute.
8. A mortar composition according to any one of the preceding claims, wherein: The clay comprises calcined clay from the kaolin group, the montmorillonite group and / or the illite group, and in particular, the clay is selected from metakaolin, calcined illite and / or calcined montmorillonite.
9. A mortar composition according to any one of the preceding claims, wherein: The aggregate comprises sand.
10. A mortar composition according to any one of the preceding claims, wherein: - the mineral binder is present in a proportion of 35 wt.% to 37 wt.% relative to the dry weight of the mortar composition; - Relative to 100 parts by weight of the cement substitute, the cement substitute comprises: 37-42 parts by weight of clay, especially calcined clay, 4-7 parts by weight of gypsum; Limestone to make up to 100 parts by weight; - Optionally, the mortar comprises 0.01 wt.% to 1 wt.% of a plasticizer additive, in particular a polycarboxylate ether, relative to the dry weight of the mortar composition; - Optionally, the mortar comprises 0.01 wt.% to 1 wt.% of a calcium compound, in particular calcium oxide and / or calcium carbonate powder, relative to the dry weight of the mortar composition; - Optionally, the mortar comprises 0.001 wt.% - 0.05 wt.% of the retarder additive, especially a hydroxycarboxylate, in particular sodium gluconate, relative to the dry weight of the mortar composition.
11. A mortar composition according to any one of the preceding claims, wherein: The mortar composition is a cementitious tile adhesive, a grouting material, a self-leveling lining, a self-leveling covering, a primer, a repair mortar, a masonry thin-joint mortar or concrete, a mortar primer, a wall leveling agent for interior or exterior, a non-shrinkage grouting, a thin-joint mortar, a waterproof mortar, or an anchoring mortar.
12. A workable mortar composition comprising a dry mortar composition according to any one of the preceding claims and water, wherein the weight ratio of water to the mineral binder is 0.25-0.7, in particular 0.3-0.
5.
13. A hardened mortar composition obtainable by hardening the workable mortar composition according to claim 12.
14. Use of the mortar composition according to any one of claims 1 to 11 or the processable mortar composition according to claim 12 as a cementitious tile adhesive, a grouting material, a self-leveling lining, a self-leveling covering, a render, a repair mortar, a masonry thin-joint mortar or concrete, a mortar primer, a wall leveling agent for interior or exterior, a non-shrinkage grout, a thin-joint mortar, a waterproof mortar, or an anchoring mortar.
15. A method for preparing a mortar composition according to any one of claims 1 to 12, wherein: 15wt.%-50wt.%, preferably 32wt.%-50wt.%, more preferably 35wt.%-50wt.%, still more preferably 35wt.%-38wt.%, especially 35wt.%-37wt.% of a mineral binder as defined in any of claims 1 to 12 is mixed with 50wt.%-80wt.%, preferably 50wt.%-68wt.%, more preferably 50wt.%-65wt.%, still more preferably 62wt.%-65wt.%, especially 63wt.%-65wt.%, of aggregate, especially sand, and optionally 0-10wt.%, especially 0-6wt.% of one or more additives, wherein all wt.% are relative to the total dry weight of the mortar composition.
Citation Information
Patent Citations
Process for modifying polymers containing acid groups
DE10015135A1
Multipurpose, cement dispersing polymers for high flow and high strength concrete
EP1061089B1
Polymers for cement dispersing admixtures
EP1138697A1
Polymers for cement dispersing admixtures
EP1138697B1
Polymers in solid changing state
EP1348729A1